Litrature Review Trauma Vascular - Hardi Tenggara, Muhammad (CV RIFAINSTITUT, 2021)
Vascular traumatic is trauma to the blood vessels caused by blunt injuries such as a hard impact or penetrating injuries such as sharp object injuries, penetrating bullet shots. Massive haemorrhage is the main cause of vascular trauma, resulting in death. Therefore, prompt treatment is needed to avoid other complications or even death due to uncontrolled bleeding. Vascular surgeons are the key to trauma injury patients, by controlling bleeding and vascular reconstruction, using aspects of open and endovascular surgical techniques. Diagnostic protocols are needed to identify injuries and consider the best tactics for surgical treatment of vascular injuries. Accurate, non-invasive diagnostic imaging techniques are key to this strategy. The aim of this review is to determine the optimal diagnostic imaging in patients with suspected vascular injury in the anatomic region and the method of treatment with retrospective or prospective data collection which is preferable to CT angiography compared to other methods. CT angiography can be declared the gold standard for diagnosing vascular injury in patients.